Protecting Indigenous Traditional Knowledge Through a Holistic Principle-Based Approach. Issue 1 (2nd January 2021) - Hossain, Kamrul; Ballardini, Rosa Maria
ABSTRACT: This article examines the legal complexity concerning protection of traditional knowledge (TK) held by Indigenous Peoples. Despite the significance of this knowledge, particularly concerning environmental conservation, biodiversity management, bioresources, and ecosystem management in connection with the traditional lands on which Indigenous Peoples live, current legal frameworks fall short of offering a comprehensive protection regime respectful of key ethical principles that are central for Indigenous Peoples, mainly fairness, the right to culture, and Indigenous Peoples' right to self-determination (IPRSD). To map the currently available solutions offered for protecting TK rights, this article primarily examines three legal regimes – intellectual property rights (IPR), human rights, and biodiversity – but also looks at some national solutions. However, none of these regimes per se offers a suitable solution, and each suffers from various shortcomings, as we demonstrate in detail. Yet if developed further, these regimes – along with some others – would indeed be suitable mechanisms for TK protection. Accordingly, this article suggests a principle-based approach to protecting and accessing TK that amalgamates the regime of human rights with the concepts of private property and exclusivity via mainstreaming values, such as fairness and the right to culture, associated with IPRSD holistically, and throughout multiple layers of legal decision-making.